The analysis of cathepsin L that mediates cellular SARS‐CoV‐2 infection leading to COVID‐19 in head and neck squamous cell carcinoma - Gao, Feng; Wang, Xia; Qin, Nianhong; Zhang, Mingxia; Liao, Mingfeng; Zeng, Meiqi; Lu, Desheng; Sha, Ou (Frontiers in Immunology, 2023)
The vulnerability of the oral cavity to SARS-CoV-2 infection is well-known, and cancer patients are at a higher risk of COVID-19, emphasizing the need to prioritize this patient population. Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignant cancers associated with early metastasis and poor prognosis. It has been established that cancerous tissues express Cathepsin L (CTSL), a proteinase that regulates cancer progression and SARS-CoV-2 entry. Therefore, it is essential to evaluate the correlation between disease outcomes and CTSL expression in cancer tissues and predict the susceptibility of cancer patients to SARS-CoV-2. In this study, we used transcriptomic and genomic data to profile CTSL expression in HNSCC and developed a CTSL signature that could reflect the response of HNSCC patients to chemotherapy and immunotherapy. Additionally, we investigated the relationship between CTSL expression and immune cell infiltration and established CTSL as a potential carcinogenic factor for HNSCC patients. These findings could aid in understanding the mechanisms underlying the increased susceptibility of HNSCC patients to SARS-CoV-2 and contribute to the development of therapy for both HNSCC and COVID-19.